Fine needle aspiration (FNA) cytology of pilomatrixoma: report of 14 cases and review of the literature - Viero, Rosa Marlene [UNESP]; Tani, E.; Skoog, L. (Blackwell Science, 1999)
We describe 14 cases of pilomatrixoma which were diagnosed preoperatively on FNA cytology. In contrast to the literature, our series showed male preponderance and some of the tumours in unusual locations such as thigh and breast. In three patients the rumours were larger than 5 cm. The clinical diagnosis varied from tumour not otherwise defined to sarcoma. The cytologic presentation had features which allowed a correct diagnosis in all cases and included basaloid cells surrounded by delicate pink fibres, shadow cells, giant cells, naked nuclei and calcium deposits. It is concluded that the FNA cytology of pilomatrixoma is characteristic and will allow a conclusive diagnosis even in cases with an aberrant clinical presentation.
Keywords: pilomatrixoma; FNA cytology; skin adnexal